Only Females Oviposit: Chemical Discrimination of Adult Stink Bug Sex by the Egg Parasitoid Trissolcus japonicus - Arif, Mokhtar Abdulsattar; Alınç, Tuğcan; Guarino, Salvatore; Colazza, Stefano; Cusumano, Antonino; Peri, Ezio (Frontiers in Ecology and Evolution, 2021)
Egg parasitoids foraging for suitable hosts scattered in the environment rely mainly on chemical cues. Elucidating the chemical ecology of natural enemies is important in the development of effective and successful strategies for conservation biological control. In this context, the host cuticular hydrocarbons, which are exploited by several species of egg parasitoids as contact kairomones, could be used to retain them by providing information about the presence and the sex of adults of the target species: sex is important because only females of the host species lay the eggs that can be subsequently utilized for parasitoid reproduction. However, the chemical basis of host sex discrimination in egg parasitoids is not well understood. We carried out behavioral and chemical bioassays to investigate the role played by contact chemical cues left by adults of the brown marmorated stink bug, Halyomorpha halys Stål, in host egg searching behavior and adult host sex discrimination by the egg parasitoid Trissolcus japonicus (Ashmead). A first set of bioassays showed that parasitoids spent more time exploring patches contaminated with chemicals associated with adult H. halys females compared with adult males. Similar responses were displayed by T. japonicus when hexane extracts of H. halys were tested suggesting that non-polar chemical compounds are involved in host sex discrimination. GC-MS analysis of hexane extracts revealed quantitative differences in the cuticular compounds of the two sexes, with 1-hexadecene (more abundant in males) being the most important component in determining these differences. Hexane extracts of H. halys females blended with synthetic 1-hexadecene significantly reduced the wasps’ arrestment responses compared to crude extracts.